KARAKTERISTIK PERMASALAHAN YANG DIHADAPI OLEH BADAN AKUNTABILITAS KEUANGAN NEGARA DPR RI DALAM MENGIMPLEMENTASIKAN KEBIJAKAN - A. Junaidi Auly; Bahrullah Akbar; Didik Suhardi; Nirva Diana (GoAcademica Research dan Publishing, 2020)
This study examines the characteristics of the problems faced by the DPR RI's State Financial Accountability Board, which has become an obstacle for BAKN in implementing policies related to state financial accountability. The research method in this study uses a qualitative approach using descriptive methods that describe the characteristics of the problem in policy implementation. The theory used is the theory of implementation proposed by Mazmanian and Sabatier. The research findings show that from the characteristics of the problem, it is known that the implementation of the MD3 policy by BAKN still has technical difficulties, including the rules including BAKN's duties only as a review. In addition, there is a diversity of behavior where the scope of BAKN review is so wide that there are even 1196 LHPs, the review task is not proportional to the number of BAKN members 10 members. It is not surprising that the scope of behavior change in this policy has not yet been achieved, especially in creating accountability for state finances.